Impact of telemedicine on clinical practice patterns for patients with chest pain in the emergency department. (May 2022) - Ostberg, Nicolai; Ip, Wui; Brown, Ian; Li, Ron
Highlights: Telemedicine within Emergency Departments has been pervasive throughout COVID-19. More orders placed for patients with chest pain who received telemedicine. Telemedicine had minimal impacts on timeliness of care provided. Telemedicine within the Emergency Department has many uses outside of COVID-19. Abstract: Background: The outbreak of the COVID-19 pandemic has led to the rapid adoption of novel telemedicine programs within the emergency department (ED) to minimize provider exposure and conserve personal protective equipment (PPE). In this study, we sought to assess how the adoption of telemedicine in the ED impacted clinical order patterns for patients with chest pain. We hypothesize that clinicians would rely more on imaging and laboratory workup for patients receiving telemedicine due to limitation in physical exams. Methods: A single-center, retrospective, propensity score matched study was designed for patients presenting with chest pain at an ED. The study period was defined between April 1st, 2020 and September 30th, 2020. The frequency of the most frequent lab, imaging, and medication orders were compared. In addition, poisson regression analysis was performed to compare the overall number of orders between the two groups. Results: 455 patients with chest pain who received telemedicine were matched to 455 similar patients without telemedicine with standardized mean difference < 0.1 for all matched covariates. The proportion of frequent lab, imaging, and medication orders were similar between the two groups. However, telemedicine patients received more orders overall (RR, 1.19, 95% CI, 1.11, 1.28, p-value < 0.001) as well as more imaging, lab, and nursing orders. The number of medication orders between the two groups remained similar. Conclusions: Frequent labs, imaging, and medications were ordered in similar proportions between the two cohorts. However, telemedicine patients had more orders placed overall. This study is an important objective assessment of the impact that telemedicine has upon clinical practice patterns and can guide future telemedicine implementation after the COVID-19 pandemic.